PU’UNO RONGA TEKALE ANO TO MORONENE: MANUSKRIP PENYELAMAT KLAIM MASYARAKAT ADAT HUKAEA - Mutmainnah, Mutmainnah (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2021)
The HukaEa indigenous people are the Moronene people who are scattered in the Poleang and Rumbia mainland areas or which are currently included in the expansion of the Bombana Regency. The community itself is a group of people with a total of 110 families with a total of 453 people who are struggling to defend their claim to their customary territory, covering an area of ​​26,000 Ha. Nowadays, the problem faced by the community is their territory which is right inside the Rawa Aopa National Park. This then became a barrier to the community in carrying out their activities, so that territorial claims were filed. In The Ministry Regulation No. 52 of 2014, it is explained that indigenous peoples must be identified through 5 elements, namely, history, territories, customary law, assets or customary objects, and customary government institutions or systems. In this case, there is a lack of written history related to the community and no one has written a history of how the HukaEa indigenous people were originally from. However, the discovered manuscript that was typed by the HukaEa community in 1974 slowly saved the HukaEa indigenous people in the process of claiming their territory and existence. In the text, entitled PU'UNO RONGA TEKALE ANO TO MORONENE, it is clear how the history of the early birth of the Moronene community in general and the formation of a group of HukaEa Indigenous Peoples who live in the area which is currently the area of ​​the Rawa Aopa National Park, as well as the history of customary government and also his royal lineage. This rewritten manuscript has now become one of the strong grips and foundations for the HukaEa indigenous people in claiming their existence as indigenous peoples who are recognized and protected by the government